Reflections on Dr J Michael Lane, a giant of public health (1936-2020) - C Raina MacIntyre (University of New South Wales, 2020)
Reflections on Dr J Michael Lane (1936-2020) a global leader in smallpox eradication and the Director of Smallpox Eradication at the US CDC. Dr Lane was an alumnus of the US CDC's Epidemic Intelligence Service and had worked in global health on control of outbreaks in many countries. He was a pivotal figure in smallpox eradication, especially in identifying the risk of continuing smallpox vaccination in the US when disease incidence was low. This article is a reflection on his global contributions to infectious diseases control.